Purwarupa Power Control Pada Electronic Power System untuk Monitoring Proses Charging/Discharging Baterai - Bakhtiar Aldino Ardi Sumbodo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2011)
AbstrakNanosatelit adalah salah satu jenis satelit yang memiliki berat kurang dari 10 kg. Sistem utama nanosatelit dapat dibagi menjadi beberapa subsistem yaitu payload, attitude determination and control system (ADCS), On-Board Data-Handling/On-Board Computer (OBDH/OBC), Ground Station dan Electronic Power System (EPS). Sistem power utama pada nanosatelit ini dikendalikan sepenuhnya oleh EPS. EPS memegang peranan penting karena unit-unit lain sangatlah bergantung pada Electrical Power System ini. Jika Electrical Power System ini mengalami kegagalan maka seluruh unit lainnya juga akan mengalami ganguan. Oleh karena itu, sebelum nanosatelit diluncurkan ke luar angkasa, maka perlu diadakan beberapa riset untuk keperluan ground testing dengan cara menguji semua sub-sistem dari nanosatelit yang dibangun termasuk kinerja charging/discharging pada baterai yang digunakan. Dalam penelitian ini akan dirancang dan dibangun purwarupa power control dari EPS untuk nanosatelit untuk memonitoring kinerja baterai dengan memantau arus dan tegangan dalam proses charging dan discharging.Kata kunci— nanosatelit, power control, electronic power system (EPS), charging/discharging baterai AbstractNanosatelit is one type of satellite that weighs less than 10 kg. Nanosatelit main system can be divided into several subsystems, namely payload, attitude determination and control system (ADCS), On-Board Computer Data-Handling/On-Board (OBDH / OBC), Ground Station and Electronic Power System (EPS). The main power system at this nanosatelit controlled entirely by the EPS. EPS plays an important role for other units is dependent on the Electrical Power System of this. If the Electrical Power System is a failure then all the other units will also experience a disturbance. Therefore, before nanosatelit launched into space, we need to hold a testing ground for research by examining all sub-systems of nanosatelit built including the performance of charging / discharging of the battery used. In this study will be designed and built prototypes for power control of EPS nanosatelit for monitoring the performance of the battery by monitoring the current and voltage in the process of charging and discharging. Keywords— nanosatelit, power control, electronic power system (EPS), charging / discharging the battery